The first 2 h after birth: prevalence and factors associated with neonatal care practices from a multicountry, facility-based, observational study. Issue 1 (January 2021) - Sacks, Emma; Mehrtash, Hedieh; Bohren, Meghan; Balde, Mamadou Dioulde; Vogel, Joshua P; Adu-Bonsaffoh, Kwame; Portela, Anayda; Aderoba, Adeniyi K; Irinyenikan, Theresa Azonima; Maung, Thae Maung; Thwin, Soe Soe; Mon, Nwe Oo; et al.
Summary: Background: Amid efforts to improve the quality of care for women and neonates during childbirth, there is growing interest in the experience of care, including respectful care practices. However, there is little research on the prevalence of practices that might constitute mistreatment of neonates. This study aims to describe the care received by neonates up to 2 h after birth in a sample of three countries in west Africa. Methods: Data from this multicountry, facility-based, observational study were collected on 15 neonatal care practices across nine facilities in Ghana, Guinea, and Nigeria, as part of WHO's wider multicountry study on how women are treated during childbirth. Women were eligible if they were admitted to the participating health facilities for childbirth, in early established labour or active labour, aged 15 years or older, and provided written informed consent on behalf of themselves and their neonate. All labour observations were continuous, one-to-one observations of women and neonates by independent data collectors. Descriptive statistics and multivariate logistic regressions were used to examine associations between these neonatal care practices, maternal and neonate characteristics, and maternal mistreatment. Early neonate deaths, stillbirths, and higher order multiple births were excluded from analysis. Findings: Data collection took place from Sept 19, 2016, to Feb 26, 2017, in Nigeria; from Aug 1, 2017, to Jan 18, 2018, in Ghana; and from July 1 to Oct 30, 2017, in Guinea. We included data for 362 women–neonate dyads (356 [98%] with available data for neonatal care practices) in Nigeria, 760 (749 [99%]) in Ghana, and 558 (522 [94%]) in Guinea. Delayed cord clamping was done for most neonates (1493 [91·8%] of 1627); other practices, such as skin-to-skin contact, were less commonly done (1048 [64·4%]). During the first 2 h after birth, separation of the mother and neonate occurred in 844 (51·9%) of 1627 cases; and was more common for mothers who were single (adjusted odds ratio [AOR; adjusting for country, maternal age, education, marital status, neonate weight at birth, and neonate sex] 1·8, 95% CI 1·3–2·6) than those who were married or cohabiting. Lack of maternal education was associated with increased likelihood of neonates not receiving recommended breastfeeding practices. Neonates with a low birthweight (<2·5 kg) were more likely (1·7, 1·1–2·8) to not begin breastfeeding on demand than full weight neonates. When women experienced physical abuse from providers within 1 h before childbirth, their neonates were more likely to be slapped (AOR 1·9, 1·1–3·9). Interpretation: A high proportion of neonates did not receive recommended care practices, and some received practices that might constitute mistreatment. Further research is needed on understanding and measuring mistreatment to improve care, including respectful care, for mothers and neonates. Funding: US Agency for International Development, and the UNDP/UN Population Fund/UNICEF/WHO/World Bank Special Programme of Research, Development and Research Training in Human Reproduction, Department of Reproductive Health and Research, WHO.